PEMETAAN KETAHANAN PANGAN BERDASARKAN ASPEK AKSES PANGAN DAN KETERSEDIAAN BERAS DI KABUPATEN OGAN KOMERING ULU - Fifian Permata Sari, Dwi Suhartinah, (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2025)
Food security in Ogan Komering Ulu (OKU) Regency has not been mapped into the Geographic Information System. Food security is a condition in which people can meet their own food needs. Therefore, as an initial step to overcome the problem of food insecurity, it is necessary to identify the condition of food security in OKU Regency. The purpose of this study is to analyze access to food and the availability of rice at the growth rate in OKU Regency. The access-utilization indicators used in this study are three indicators, namely: 1) poor population, 2) population working less than 15 hours a week, and 3) population not graduating from elementary school. This research method is descriptive quantitative. The data used in this study are secondary data obtained from related agencies. The results of this study indicate that there are four sub-districts with a rice surplus with a composite index of less than 1, while nine sub-districts are rice deficits with a composite index of more than 1. In terms of access, six sub-districts are in good access conditions with a composite of less than 1, and seven others are in poor access with an index of more than 1. Based on the relative conditions of the combination and availability of rice and access to rice, one sub-district is in a safe position, namely West Baturaja, while there are eight sub-districts that are in an alert position, and four sub-districts are in an unsafe position. The combination of rice availability and rice access to food security shows that OKU Regency is in an urgent condition.